Evaluation of Internal Audit in Reducing SOP Violations and Fraud at PT XYZ - Nusa, Mega Sari (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
From 2016 to 2017, there were cases of procedural violations and embezzlement for the tax payments at PT XYZ. This study aims to evaluate the internal audit and internal control in PT XYZ’ tax payment cycle by using 5 (five) important factors, namely Segregation of Duties, Policies and Procedures, Documentation, Oversight and Review and User Access and Rights, in establishing and proving the effectiveness of the firm’s internal control. This research is a case study with a qualitative approach conducted at PT XYZ with the unit of analysis at the tax division. The data collection method was done through a semi-structured interview, checklist, and documentation, with descriptive qualitative analysis being the data analysis technique applied. The results of this study indicated that the internal control system at PT XYZ has a significant weakness in the cash disbursement process on tax payments which opens up opportunities of manipulation (fraud) by certain employees of the tax division. Additionally, the tax division is outside the scope of internal audit work which shows inadequacy and ineffectiveness from the design of the internal control system. PT XYZ's internal audit team substantially does not have the competence to reach the "expert" level in accordance with the criteria outlined by the IIA, as the function to prevent fraud is still being managed aptly but the aptness is only constrained for the 3S activities: Service, Sales, and Spareparts.